2020
DOI: 10.1098/rsta.2019.0470
|View full text |Cite
|
Sign up to set email alerts
|

Boltzmann equation and hydrodynamic equations: their equilibrium and non-equilibrium behaviour

Abstract: This short article summarizes the key features of equilibrium and non-equilibrium aspects of Boltzmann and hydrodynamic equations. Under equilibrium, the Boltzmann equation generates uncorrelated random velocity that corresponds to k 2 energy spectrum for the Euler equation. The latter spectrum is produced using initial configuration with many Fourier modes of equal amplitudes but with random phases. However, for a large-scale vortex as an initial condition, earlier simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…For example, Cichowlas et al [58] showed that Taylor-Green vortex as an initial condition yields a mixture of k −5/3 and k 2 spectra. On the contrary, for white noise as initial condition, the system exhibits k 2 spectrum for the whole range of wavenumbers [59,60]. The former system exhibits variable energy flux, but the latter system (equilibrium configuration) has no energy flux.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Cichowlas et al [58] showed that Taylor-Green vortex as an initial condition yields a mixture of k −5/3 and k 2 spectra. On the contrary, for white noise as initial condition, the system exhibits k 2 spectrum for the whole range of wavenumbers [59,60]. The former system exhibits variable energy flux, but the latter system (equilibrium configuration) has no energy flux.…”
Section: Introductionmentioning
confidence: 98%
“…Later, Kraichnan [4] proposed a different approach for these absolute equilibrium states by considering that the complex amplitudes of the Fourier modes followed a canonical distribution that is controlled by the mean values of the invariants of the system. The Galerkin-truncated hydrodynamical system that has been investigated most extensively is the time-reversible Euler equation for a classical, ideal fluid [68], which can be studied efficiently, in a spatially periodic domain, by the Fourier pseudospectral method [9,10]. Absolute-equilibrium solutions have also been examined in a variety of hydrodynamical systems including compressible flows [11], the Gross-Pitaevskii equation in both three and two dimensions [12,13], and the Euler equation and ideal magnetohydrodynamics (MHD) in two dimensions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodynamic and Burgers turbulence, crack propagation, and earthquakes are some of the prominent examples of nonequilibrium systems. Interestingly, dissipation-less hydrodynamic and Burgers turbulence exhibit both nonequilibrium and equilibrium behaviour depending on the initial condition [2][3][4]. This is the subject of this paper.…”
Section: Introductionmentioning
confidence: 91%
“…Clearly, the equilibrium configurations of the KdV and dissipation-less Burgers equations discussed above are very similar to that of Euler turbulence. Verma [4] and Verma et al [27] simulated Euler turbulence using delta-correlated random initial condition and obtained the aforementioned equilibrium state. Note that a smooth large-scale velocity field as an initial condition, as in Cichowlas et al [2], yields nonzero energy flux as transients.…”
Section: Energy Fluxes In Kdv and Burgers Turbulencementioning
confidence: 99%
See 1 more Smart Citation